Relationship between psychovegetative status dysfunction and markers of the early formation of the atherosclerotic process in flight personnel in the Far North - Yu. N. Zakrevsky; A. V. Gertsev; V. P. Boutikov; V. M. Manuilov; Ю. Н. Закревский; А. В. Герцев; В. П. Бутиков; В. М. Мануйлов (Marine Medicine, 2021)
The aim of this work is studying the influence of the severity of dysfunctions on the part of the central and autonomic nervous systems on the atherosclerotic process in hypertension in flight crews with concomitant traditional factors of cardiovascular risk (abdominal obesity) serving in the Far North by the authors.Materials and methods. A clinical examination was carried out on 54 patients (men) aged from 33 to 42 years, from among the military personnel of the aviation personnel of the Northern Fleet naval aviation, the average age of the examined was 37.4±4.6 years. The following groups of patients were formed: 1st (n=26) — flight crew specialists serving in the Far North, with first degree abdominal obesity, first stage hypertension and moderate astheno-neurotic disorders (main group); 2nd (n=14) — flight crew specialists serving in the Far North, with first degree abdominal obesity, first stage hypertension in comorbidity with mild astheno-neurotic disorders; Group 3 (n=10) was represented by flight crew patients with the first stage of hypertension with initial manifestations of psychovegetative dysfunctions (control). We assessed the qualitative and quantitative paired correlations between the state of the psychological status, regulation of the neuropsychic adaptation system, markers of early formation of atherosclerosis, and indicators of the average daily blood pressure level.Results and their discussion. It was found that the severity of disorders of the asthenovegetative spectrum in the examined groups has a negative direct pathological effect on quantitative and qualitative paired correlations between indicators characterizing the state of psychophysiological status, markers of early formation of the atherosclerotic process, and values of average daily blood pressure monitoring. The results obtained make it possible to summarize that the more pronounced the disturbances in the functioning of the central and autonomic nervous systems in hypertension in persons from the flight crew, the more ...